Adrenocortical suppression increases the risk of relapse in nephrotic syndrome. Issue 7 (6th February 2007) - Abeyagunawardena, Asiri S; Hindmarsh, Peter; Trompeter, Richard S
Abstract : Objective: Children with nephrotic syndrome (NS) are usually treated with long-term low dose alternate day prednisolone with or without glucocorticoid sparing therapy, such as levamisole or ciclosporin, to maintain remission. The degree of hypothalamic-pituitary-adrenal axis (HPA) suppression with such therapeutic strategies has not been studied systematically. HPA suppression could cause a relapse or adrenal crisis. Study design: To study the risks of HPA suppression, a modified low dose synacthen test (0.5 μg) was administered to 32 patients (22 male, 10 female) with a mean age of 9.7 years (range 3.8–17.6 years) with NS receiving long-term alternate day prednisolone for over 12 months. Twelve patients received alternate day prednisolone, 11 alternate prednisolone+levamisole and nine alternate prednisolone+ciclosporin. All patients were followed up for 3 years and the relapse rate noted. Results: 20/32 (62.5%) patients had a peak serum cortisol concentration of <500 nmol/l, which suggested suboptimal cortisol secretion and possible HPA suppression. 10/12 children in the prednisolone group and 8/11 in the levamisole group had a suboptimal cortisol response compared with 2/9 in the ciclosporin group. During follow-up, the 20 children who had a suboptimal cortisol response had significantly more relapses (95 relapses) compared to the 12 children with a normal cortisol response who had 24 relapses (p = 0.01). Conclusions: Children with NS receiving long-term alternate day prednisolone therapy are at risk of developing HPA suppression and should be evaluated using the modified synacthen test. Children with evidence of HPA suppression are at a greater risk of relapse.